Conversions to Islam in Bosnia and Herzegovina and connections of converts with their Christian family, from the Ottoman conquest to the end of the 17th century (Povijesni prilozi (Historical Contributions), 2019)
Based on the available documents, the author has analysed the connections betweenconverts to Islam and the Christian part of their families, and the way in which the conversionsinfluenced the lives of converts and their Christian relatives. Adopting anotherreligion did not mean abandoning the old habits and Christian traditions. Regardlessof the change of religion and the new religious practices they had to follow, there werethose who continued living in accordance with the Christian tradition. The converts’contacts with their Christian families contributed to that considerably. The diff erencein name and religion did not break family ties even when families were separated.